ISU HAM DALAM POLITIK LUAR NEGERI ASTERHADAP INDONESIA ERA 1990-AN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The disappearance of communism threat following the fall of the Soviet Union has forced the United States to review its policies on countries that previously spoiled by foreign aid, such as Indonesia. During the cold war the United States tolerated human rights violations in Indonesia, but when the cold war ended, the United States became very critical and even threatened to stop her military aid. This study intends to look for factors that lead the US so concern on human rights issues in relation with Indonesia during 1990s and how US use human rights issues to press Indonesia. Then this study tries to see what Indonesia's reaction in facing the pressures relating to human rights in this country, what the strategy Indonesia has taken. Based on the data, and it can be concluded that the disappearing communism threat and the significance of fulfilling domestic economic need were two important points that led to the change of American attitude against Indonesia in human rights practice. Although Indonesia took position and clearly denied human rights conditionality in foreign aid, Indonesia still developed adaptive and accommodative attitude in facing pressures and critics from abroad by giving a priority to Indonesia's national interest consideration. Keywords: foreign policy - post cold war - national interest - human rights - foreign aid